Construction of Air Pollution Index with the Inclusion of Aggregated Weights of the Pollutants (Journal of Information and Communication Technology, 2022)
The ambient air quality measurement in Malaysia is described as Air Pollution Index (API). Basically the existing API for a given period of time is defined as the maximum value of the sub-index values of six pollutants. Although research has shown that long and short term exposure to air suspended toxicants has a different toxicological impact on human, the API still considers these pollutants as having equal hazardous impacts on human. Hence, this paper aims to propose a new API that includes weights representing different hazardous levels of these pollutants in its calculation. Based on secondary data of six pollutants’ readings for sixteen states of Malaysia for year 2018, the aggregated weights were computed by combining both weights obtained from the subjective experts’ opinions and the objective data-driven methods, which balanced both perspectives of evaluations. The results show that the particulate matter with aerodynamic diameter less than 2.5 micrometre (PM2.5) found to be the most hazardous pollutant since its aggregated weight value is the highest and the distributions of the API readings for all sixteen states were found to be normal. The highest and lowest API readings took place on the 14th of August and 10 of March 2018 respectively. It is argued that the new API readings are more accurate and give a better picture about the occurrence of air pollution in Malaysia in particular. This study provides a new insight in constructing API specifically and contributes a more comprehensive and precise air quality measurements to be analysed by the responsible authorities in their efforts towards healthy environment.